2023
DOI: 10.3390/ma16031239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Treatment on the Mechanical Properties of Bamboo Fiber Bundles

Abstract: Bamboo is known as a typical kind of functional gradient natural composite. In this paper, fiber bundles were extracted manually from various parts of the stem in the radial direction, namely the outer, middle, and inner parts. After heat treatment, the mechanical properties of the fiber bundles were studied, including the tensile strength, elastic modulus, and fracture modes. The micromechanical properties of the fiber cell walls were also analyzed. The results showed that the mean tensile strength of the bam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The failure mode is also a general concern in bamboo specimens tested in axial loading. Zhou et al [54] observed a ductile failure characteristic in Phyllostachys edulis bamboo tested in parallel to grain, similar to the observation of Cui et al [11] on bamboo fiber bundles. Basically, the common mode of failure of bamboo culms tested in parallel to the grain is splitting and end bearing [14,45,82,85].…”
Section: Bamboo Culmssupporting
confidence: 67%
See 1 more Smart Citation
“…The failure mode is also a general concern in bamboo specimens tested in axial loading. Zhou et al [54] observed a ductile failure characteristic in Phyllostachys edulis bamboo tested in parallel to grain, similar to the observation of Cui et al [11] on bamboo fiber bundles. Basically, the common mode of failure of bamboo culms tested in parallel to the grain is splitting and end bearing [14,45,82,85].…”
Section: Bamboo Culmssupporting
confidence: 67%
“…Krause et al [10] mentioned that the tensile behavior of Dendrocalamus gigantus is dictated by the fiber volume fractions and independent of the position of the culm wall. Cui et al [11] observed that the tensile strength of bamboo fiber bundles gradually decreases with increasing temperature, which is mainly influenced by the decrease in the relative content of cellulose and hemicellulose. Wu et al [12] confirmed that the tensile strength of an outer bamboo sliver treated with alkali at 60 • C and an inner bamboo sliver treated with alkali at 40 • C will increase up to a maximum of 86.6% and 132%, respectively, compared to untreated bamboo.…”
Section: Introductionmentioning
confidence: 99%
“…The mass loss increases with increasing temperature with significant mass loss observed at holding temperature above 250 °C. The high temperature processing resulted in the thermal degradation of fiber structure, loosening of the cell wall, and generation of pores (Cui et al 2023). Furthermore, tensile tests were performed to investigate the changes in mechanical properties of the bamboo fiber, with results shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glubam [13][14][15][16] LBL [17][18][19] Douglas Fir [20] WPC [21] Tensile Due to the mechanical properties [27][28][29][30][31][32][33][34] of the fiber are obviously superior to those of the matrix, there are significant differences in the fracture characteristics of bamboo fibrous composites along and perpendicular to the fiber direction. In addition, this difference is influenced by the distribution of fibers, showing a more complex mode of variation.…”
Section: Methodsmentioning
confidence: 99%